Hubungan Kimpetensi Sosial Guru PAI Dengan Minat Belajar Siswa Kelas IX SMPN 1 Telukjambe Timur Karawang - Bibil Muhammad Jibril; Sutarjo .; Lilis Karwati (Jurnal Ilmiah Wahana Pendidikan, 2022)
The teacher is the most vital figure in the world of education. Teachers are professionals whose duties are to educate, teach, guide, direct, assess and evaluate students in early childhood formal education, primary and secondary education (RI Law Number 14 of 2005 concerning Teachers and Lecturers). Professional teachers must have competencies, where the competence of the teacher has 4 kinds of competences. The first is personality competence, pedagogical competence, professional competence and social competence. The Relationship between PAI Teachers' Professional Competence and Learning Interest This study used a quantitative design with a questionnaire questionnaire. The total sample used in this study amounted to 80 class IX students consisting of 3 classes. The PAI Teacher Professional Competence Variable was measured through a questionnaire questionnaire from Variable X using research instruments and the Learning Interest Variable was measured through a questionnaire questionnaire variable Y with 10 items each of each variable. Testing requirements analysis for data normality tests using educational statistical tests in the exel program. Then do the analysis of the Sperman Rank Correlation Summary test. To find out the results of hypothesis testing, it shows that the relationship between the PAI Teacher Professional Competence learning model and student interest in learning. In the Sperman Rank Correlation table, the conclusion is: Hypothesis testing is accepted if the t value ≥ t table. From the results of the above calculations show that t count = 7.5 ≥ t table 1.9916. This means that there is an interaction relationship between PAI Teacher Professional Competence and Student Learning Interests.